2019
DOI: 10.1039/c9qi00370c
|View full text |Cite
|
Sign up to set email alerts
|

Novel nickel–cobalt phosphite with face-sharing octahedra derived electrocatalyst for efficient water splitting

Abstract: Nickel–cobalt phosphite (CoNiPO) including local structural motifs with face-sharing octahedra shows excellent OER activity. The derivatized electrocatalyst (NiP2@CoNiPO) exhibits high HER activity. DFT calculations indicated the super-exchange effect in CoNiPO can adjust local electronic structure and improve their catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…In addition to the single metal phosphides, the bi‐metal systems observed better in the electrocatalytic performance with high number of surface area and the conductivity [49,55,76,93,112,113] . There are very few reports with the findings of such synergistic effect of this bi‐metal system and their activity in the electrocatalytic water splitting [53,114–118] . Following are the reported work in NiCoP electrocatalyst system as a bi‐functional catalyst for overall‐water splitting reaction [53,75,119] .…”
Section: Transition Metal Phosphide Electrocatalyst For Twsmentioning
confidence: 96%
“…In addition to the single metal phosphides, the bi‐metal systems observed better in the electrocatalytic performance with high number of surface area and the conductivity [49,55,76,93,112,113] . There are very few reports with the findings of such synergistic effect of this bi‐metal system and their activity in the electrocatalytic water splitting [53,114–118] . Following are the reported work in NiCoP electrocatalyst system as a bi‐functional catalyst for overall‐water splitting reaction [53,75,119] .…”
Section: Transition Metal Phosphide Electrocatalyst For Twsmentioning
confidence: 96%
“…J. Wu et al. have studied the effect of metal octahedral structural linkage in Ni−Co−P−O compounds on their OER electrocatalytic activity and shown that face sharing octahedra of Ni and Co in Ni−Co phosphites ((Co/Ni) 11 (HPO 3 ) 8 (OH) 6 ) favor improved OER due to the super exchange effect of Co−O−Ni . Majority of the reports on Ni or Co−Phi are focused on their performance as energy storage materials such as supercapacitors and batteries .…”
Section: Introductionmentioning
confidence: 99%
“…This structure evolution is experimentally realized for the first time, and then these materials were conducted for a typical multi-phase reaction of water splitting. [6] Benefitting from the structure advantages, the CoP HoMSs with close duplicated shells facilitate the escape of gas bubbles because of unbalanced Laplace pressure, [7] and enhance the driving force for liquid diffusion [8] due to capillary action, thus achieving excellent catalytic performance in both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER).…”
mentioning
confidence: 99%